Rencana Pengembangan dan Kesiapan Sivitas Akademika UIN Raden Intan Lampung Menuju AUN-QA - Makbuloh, Deden; Sucipto, Sucipto; ruswanto, ruswanto (Universitas Islam Negeri Raden Intan Lampung, 2017)
Raden Intan Lampung State Islamic University (UIN RIL) as a State Islamic Religious College in Indonesia needs to gradually carry out various efforts to improve the quality of continuing education. The long-term quality of UIN RIL does not only cover national level competition, but also internationally. This study aims to examine the quality improvement process that has had a development and readiness plan for AUN-QA for the Academic Community of UIN RIL. Data collected is qualitative data. In accordance with the research design in order to find an overview of the planned development of UIN RIL and its readiness towards AUN-QA. The data sources in this study were taken from strategic planning documents and the opinions of the academics. Techniques for collecting data through documentation studies, deep interview, and participant observation. Non-structured interviews, so that data sources actively construct the cognitive world, and researchers try to capture the realm of that meaning. Analysis of data is collected simultaneously while collecting data with the principle of verstehen. The results of the study concluded that since the form changed from IAIN to UIN RIL development plans were discussed which were discussed in several stages and involved various stakeholders directed to the campus as an international reference. This can be seen in the vision, mission and objectives of UIN RIL. Likewise in priority programs and target targets there are points towards international scale achievements. The academics have welcomed with joy the change in form of IAIN to UIN RIL. All have stated that this is an opportunity to further develop the campus to reach international competition. Thoughts and energy were mobilized to develop UIN RIL towards becoming superior and competitive.